Biochemical and hematological parameters in the 1st trimester of pregnancy - Ivanišević, Jasmina; Ardalić, Daniela; Zeljković, Aleksandra; Vekić, Jelena; Gojković, Tamara; Vladimirov, Sandra; Antonić, Tamara; Munjas, Jelena; Stefanović, Aleksandra (Archives of Pharmacy, 2023)
The 1st trimester of pregnancy is accompanied with changes in different biochemical and hematological parameters. Analyses scheduled to be performed in the 1st trimester are complete blood count, blood group, Rh factor and the double test. Many experts also suggest the determination of lipid status parameters as a routine analysis in the early pregnancy. Reliable data about maternal and fetal health can be obtained by the assessment of the above-mentioned parameters. They may be helpful in assessing the risk for pregnancy complication development and/or perinatal adverse outcomes.
Keywords: 1st trimester of pregnancy; routine tests; lipid status parameters